A study on retirement savings behaviour: a case Shah Alam / Nur Aina Syuhadah Abdul Rahman and Nur Atik Tikka Rambe Mohd Juanda - Abdul Rahman, Nur Aina Syuhadah; Mohd Juanda, Nur Atik Tikka Rambe (2022)
Social protection schemes in Malaysia have been established in order for the society to have better plan protection for their retirement savings. Only 60.8% of Malaysia's employees are actively contributing their monthly income to the EPF. 73% of members after the three exceptional withdrawals have insufficient funds to retire above the poverty line income. At the end of 2021 54% of EPF members at the age of 54 has less than RM50, 000 in their account for retirement savings. The majority of Malaysian workers cannot afford the life after retirement. Average savings amounted to RM 194,000 equal to RM 25 per day and RM 810 per month. Besides that, it is estimated 46% of EPF members below age 55 have less than RM 10,000 in the account. The proportion of EPF members achieving the Basic Retirement funds (RM240, 000 at 55 years old) has dropped from 36% to 27%. The minimum pension for those who serve more than 25 years is RM 1000. It is concerning since monthly pension recipients have less than PLI which means most cannot provide quality necessities. Insight into the research to identify the relationship between retirement saving behaviors and financial literacy as well as financial literacy, social influence, and risk tolerance. This research also highlights the various stages of the research, such as the participant selection process, data collection, and data analysis. This research used a stratified sampling and simple random sampling for the people who are working and stay in Shah Alam. Therefore, current statistics show the population of Shah Alam is 617 149 which consists of 390 samples by Krejcie and Morgan (1970). The studies conclude with a discussion of the validity and reliability of quantitative research. The purpose of this research is to identify whether people in Shah Alam have adequate savings to live a decent life after their retirement. The study aims to determine the relationship between financial literacy and retirement saving behavior of people in Shah Alam. The main findings of this study are to discover significance for the relation between dependent variable (Retirement savings behavior) and independent variable (financial literacy, social influence and risk tolerance). It indicates that all three independent variables have significant differences that affect the retirement savings behavior.